Gonadal Sex Differentiation: Supporting Versus Steroidogenic Cell Lineage Specification in Mammals and Birds - Estermann, Martin A.; Major, Andrew T.; Smith, Craig A. (Frontiers in Cell and Developmental Biology, 2020)
The gonads of vertebrate embryos are unique among organs because they have a developmental choice; ovary or testis formation. Given the importance of proper gonad formation for sexual development and reproduction, considerable research has been conducted over the years to elucidate the genetic and cellular mechanisms of gonad formation and sexual differentiation. While the molecular trigger for gonadal sex differentiation into ovary of testis can vary among vertebrates, from egg temperature to sex-chromosome linked master genes, the downstream molecular pathways are largely conserved. The cell biology of gonadal formation and differentiation has long thought to also be conserved. However, recent discoveries point to divergent mechanisms of gonad formation, at least among birds and mammals. In this mini-review, we provide an overview of cell lineage allocation during gonadal sex differentiation in the mouse model, focusing on the key supporting and steroidogenic cells and drawing on recent insights provided by single cell RNA-sequencing. We compare this data with emerging information in the chicken model. We highlight surprising differences in cell lineage specification between species and identify gaps in our current understanding of the cell biology underlying gonadogenesis.